29.2k views
2 votes
Enter the values for the highlighted variables to complete the steps to find the sum:

Enter the values for the highlighted variables to complete the steps to find the sum-example-1

1 Answer

2 votes

Answer:

  • a = -1
  • b = -9
  • c = 9
  • d = 3
  • e = 3
  • f = 2
  • g = 3/2 = 1.5

Explanation:

For "a", we recognize that 6-2x is the opposite of 2x-6, so multiplying the latter by -1 will give the former. a = -1

For "b", we notice the denominator no longer has -1 as a factor. Rather, that has be applied to the numerator, which is now -9. b = -9

For "c" we have combined the two numerators over the common denominator. Note that the sign is already provided. 3x +(-9) = 3x -9. c = 9

For "d" and "e", we recognize that 3 is a factor of both terms of the numerator of the previous expression. Here, we factor that out. d = 3, e = 3

The common factor of the terms in the denominator is factored out to find "f". That value is 2. f = 2

The numerator and denominator factors of (x -3) have been cancelled in the last step, leaving the result d/f = 3/2. This is the value of the simplified expression, hence the value of g. g = 3/2 = 1.5

_____

Comment on g

We don't know if your answer checker is able to accept fractions as input, so we have expressed g both as a fraction and as a decimal number.

User Virag Brahme
by
6.2k points